Ultrasonographic Evaluation of Therapeutic Effects of Complex Decongestive Therapy in Breast Cancer-Related Lymphedema - Lee, Jae Hyun (Korean Academy of Rehabilitation Medicine, 2013)
OBJECTIVE: To evaluate the usefulness of ultrasonography as a follow-up tool for evaluating the effects of complex decongestive physiotherapy (CDPT) in breast cancer-related lymphedema (BCRL). METHODS: Twenty patients with BCRL were enrolled in this study. All patients had undergone therapy in the CDPT program for 2 weeks. Soft tissue thickness of both the affected and unaffected upper limb was measured before and after CDPT. The measurements were taken at 3 points (the mid-point between the medial and lateral epicondyles at the elbow level, 10 cm proximal and 10 cm distal to the elbow) with and without pressure. We then calculated the compliance of soft tissue before and after CDPT. Circumferences of both the affected and unaffected upper limb were also measured before and after CDPT at the 3 defined points. RESULTS: After 2 weeks of the CDPT program, the circumference and soft tissue thickness of the unaffected upper limb did not significantly change. In the affected upper limb, the circumference was significantly reduced in the 3 point, when compared with measurements taken prior to treatment. Additionally, soft tissue thickness was significantly reduced at the elbow and 10 cm proximal to the elbow. After CDPT, compliance at each of the 3 points had increased, but this trend was not significantly different. CONCLUSION: Our results showed that arm circumference and ultrasonography-derived soft tissue thickness was useful as a way of assessing therapeutic effects of CDPT.